Klasifikasi Kinerja Pengajaran Dosen Menggunakan Metode ANFIS Sebagai Upaya Peningkatan Sistem Penjaminan Mutu Internal (SPMI) - Ida Afriliana; Arfan Haqiqi Sulasmoro; Ali Sofyan (Politeknik Negeri Cilacap, 2019)
A college is a place for education providers that aim to produce quality human resources and be able to face increasingly fierce work competition. Lecturers become one of the important elements in producing competent human resources. The task of the lecturer is to carry out the Tri Dharma of Higher Education which includes teaching, research and community service. The purpose of this study was to obtain a teaching performance classification of lecturers using the Adaptive Neuro-Fuzzy Inference System (ANFIS) method as an effort to improve the internal quality assurance system. Where in this learning process planning, implementation, evaluation, control and improvement have been carried out as a form of implementation of the Internal Quality Assurance System (SPMI). The data used in this study are data from the questionnaire sheets of lecturers' reaction sheets from students to the teaching of lecturers who support courses. The data used is data for 1 academic year, namely data for the 2017 2018 academic year. The results of this study are that ANFIS is suitable for classifying lecturers' performance.